Inadequate anticoagulation by Vitamin K Antagonists is associated with Major Adverse Cardiovascular Events in patients with atrial fibrillation. (15th December 2015) - Pastori, Daniele; Pignatelli, Pasquale; Saliola, Mirella; Carnevale, Roberto; Vicario, Tommasa; Del Ben, Maria; Cangemi, Roberto; Barillà, Francesco; Lip, Gregory Y.H.; Violi, Francesco
Abstract: Background: Time in therapeutic range (TTR) reflects the quality of anticoagulation and is inversely correlated with ischemic stroke in atrial fibrillation (AF) patients. Few data on the relationship between TTR and myocardial infarction (MI) are available. We investigated the association between TTR and Major Adverse Cardiovascular Events (MACE) in a cohort of anticoagulated AF patients. Methods: We calculated TTR for 627 AF patients on vitamin K antagonists, who were followed for a median of 30.8 months (1755 patients/year). The primary outcome was a combined endpoint of MACE including fatal/nonfatal MI and cardiovascular death. Results: Mean age was 73.3 (± 8.2) years, and 40.2% were women. During follow-up, we recorded 67 events: 19 stroke/TIA (1.1%/year) and 48 MACE (2.9%/year): 24 MI and 24 cardiovascular deaths. The cohort was categorized according to tertiles of TTR values: TTR 13–58%, 59–74%, and 75–100%. There was a significant increased rate of MACE across tertiles of TTR (Log-Rank test: p < 0.001). On Cox proportion hazard analysis, the 2nd vs. 1st tertile of TTR (p = 0.002, hazard ratio [HR] 0.347, confidence interval [CI] 95% 0.177–0.680), 3rd vs. 1st tertile of TTR (p < 0.001, HR 0.164, CI 95% 0.067–0.402), age (p < 0.001, HR 1.094, CI 95% 1.042–1.148), history of stroke/TIA (p = 0.015, HR 2.294, CI 95% 1.172–4.490) and smoking (p = 0.003, HR 3.450, CI 95% 1.532–7.769) predicted MACE. Conclusion: TTR was an independent predictor of MACE in our cohort of AF patients. Our findings suggest that a good anticoagulation control is necessary to reduce not only the risk of stroke but also that of MACE.